Integrated Weed Seed Impact Mills for Southeast Asian Rice Systems: Could They Aid Sustainable Weed Management? - Leigh Vial; Jhoana Opeña; Jaquie Mitchell (Agronomy)
Weed management is a persistent challenge in Southeast Asian rice production, particularly in direct-seeded rice (DSR), due to the diversity of weed species and variable field and environmental conditions that can compromise weed control, necessitating innovative solutions. An integrated weed seed impact mill (iWSIM) reduces weed seed banks by destroying weed seeds during the harvest process. This mixed study is the first to fully explore the applicability of iWSIM technology in Southeast Asian rice systems, focusing on both combine harvester and iWSIM specifications and operation, determinants of efficacy, and field and harvest conditions. Weed seed bank reduction with an iWSIM depends on several factors, including weed seed retention and subsequent capture by the combine at harvest, weed seed separation into the chaff fraction, and the iWSIM’s efficacy against weed seeds captured in the chaff fraction. Observations from Southeast Asia indicate variable seed retention among key weed species, presenting challenges for harvesting strategies and iWSIM effectiveness. To optimize the iWSIM efficacy, recommendations include larger fields to reduce the weed seed produced on bunds, achieving complete early-season weed control, lowering the harvest header height to about 15 cm to capture more weed seeds, cleaning mechanism adjustments to ensure weed seeds are retained in the chaff fraction, and greater combine harvester engine power to allow a lower header height and power the iWSIM. The estimated weed control benefits of the iWSIM should also be weighed against additional equipment operating costs. iWSIM technology holds promise as part of a sustainable solution for weed control in Southeast Asian rice, contingent upon further region-specific research and adaptation.